Malpositioned Intrauterine Device: Risk Factors, Management, and Outcomes [242]. (May 2015) - Desai, Anagha; Khangura, Raminder Kaur; Craig, Brian; Sandberg, Sharon; Sangha, Roopina
Abstract : INTRODUCTION: Malpositioned intrauterine devices (IUDs) are a common clinical problem seen by gynecologists. The objective of this study was to perform a retrospective chart review for documented radiographically confirmed malpositioned IUDs in patients in Detroit, Michigan. The charts were reviewed for presenting symptoms, risk factors, IUD position, imaging modality, and the effects on clinical outcome. METHODS: Investigators performed a retrospective chart review using International Classification of Diseases, 9th Revision codes from 2010 to 2014 at Henry Ford Health System, Michigan. Charts were reviewed for presenting symptoms (pain, inability to feel IUD strings, vaginal bleeding, dyspareunia), risk factors for malpositioned IUDs (including, but not limited to, age, parity, body mass index, indication for placement, type of IUD, level of training of the health care provider), and clinical outcomes (removal compared with nonremoval). Bivariate comparisons were done using Fisher's exact tests. RESULTS: Possible risk factors investigated for malpositioned IUDs included higher parity (multigravida women 91%), level of training of the health care provider (physicians 76%), and indication for placement (contraception 86% compared with menorrhagia 14%). Chief complaints included pain (36%), IUD string nonvisualization (13%), vaginal bleeding (35%), and dyspareunia (3%). Position of the IUD was found to be cervical (30%), lower uterine segment (33%), myometrial penetration (73%), or all of these. Eleven percent were noted to be pregnant (8% intrauterine pregnancy and 3% ectopic pregnancies). Clinical outcomes included removal of IUD in 83 (laparoscopy 49%, laparotomy 4%, hysteroscopy 22%, and instrument removal 25%). CONCLUSION: Patients present with a variety of symptoms with malpositioned IUDs and have significant clinical heterogeneity regarding risk factors. Clinically, practitioners should be aware of the variety of presentations and influence of demographic varietals that may affect a women's risk for malpositioned IUDs.